2024
DOI: 10.47814/ijssrr.v6i12.1840
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Literacy on the Ability to Detect Investment Fraud

Aida Nursanti,
Irwan Trinugroho

Abstract: The financial sector has been increasingly digitized over the last few years, and the volume of fraudulent operations has also increased, which can have severe consequences. People's digital lives are growing along with the proliferation of the internet and other digital media, giving rise to increasingly sophisticated forms of fraud as a result of the increasing availability of various financial services, which of course will be detrimental to potential investors who want to develop their businesses due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…According to him, unlike the traditional criminal gangs, both male and female are functionally involved in internet fraud. Nursanti and Trinugroho (2024) in their "The effect of financial literacy on the ability to detect investment fraud" research found that individuals with higher levels of financial literacy demonstrate a greater ability to detect investment fraud. They also found that socio-demographic characteristics such as gender, age, and education have no significant effect on controlling the effect of financial literacy on the capacity to detect investment fraud.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to him, unlike the traditional criminal gangs, both male and female are functionally involved in internet fraud. Nursanti and Trinugroho (2024) in their "The effect of financial literacy on the ability to detect investment fraud" research found that individuals with higher levels of financial literacy demonstrate a greater ability to detect investment fraud. They also found that socio-demographic characteristics such as gender, age, and education have no significant effect on controlling the effect of financial literacy on the capacity to detect investment fraud.…”
Section: Literature Reviewmentioning
confidence: 99%